The Relationship between Digital Literacy and Digital Citizenship Levels of STEM Teacher Candidates: The Mediating Role of Digital Teaching Material Development Self-Efficacy - Erol Kocoglu; Sibel Oguz-Hacat; Veysel Gocer (Journal of Education in Science, Environment and Health)
In this study, it was aimed to determine the relationship between digital literacy and digital citizenship and digital teaching material development self-efficacy of the STEM teacher candidates. In the study, a correlational model was used. The population of the study consists of teacher candidates studying in different teacher training programs (Science education, Technology education, Mathematics education, Engineering education) at state universities in Turkey in the 2022-2023 academic year. The sample of the study, as for that, consists of 1050 teacher candidates who are determined by simple random sampling from the population. The study data were collected with “Digital Literacy," “Digital Citizenship," and “Digital Teaching Material Development Self-Efficacy” scales. According to the hierarchical multiple regression analysis results, it was determined that the level of digital literacy and digital material development self-efficacy significantly predicted the digital citizenship level. Besides, in the study, it was determined that digital material development self-efficacy plays a partially mediating role in the relationship between digital literacy and digital citizenship behavior. According to the study results, it was suggested that the teacher candidates’ work on increasing digital literacy levels would be beneficial to improve their digital citizenship and digital material development self-efficacies